TYPICAL INVESTIGATIVE SITUATIONS DURING THE INITIAL STAGE OF TERRORISM FINANCING INVESTIGATION (Bulletin of criminological association of Ukraine, 2025)
The article highlights factors that influence the complexity of investigating crimes related to terrorism financing, especially in the context of modern technologies, cryptocurrencies, fictitious companies, and cross-border schemes. It stresses the importance of applying a scientifically sound methodological approach based on typifying investigative situations encountered at the early stages of the pre-trial investigation. This helps systematize information, enhance tactical decision-making, and reduce errors. The article identifies main types of investigative situations–simple/complex, obvious/not obvious, favorable/unfavorable–and describes their key characteristics. It notes the high resistance from criminals, difficulty accessing evidence, and the necessity for a decisive law enforcement response amid armed conflict against Ukraine. The situational approach proposed aims to improve investigation efficiency, safeguard national security, and limit misuse of procedural tools like plea agreements.
Keywords: crime; terrorism; terrorist financing; forensic methodology; initial stage of investigation; investigative situation; version